Law relating to banking in Hong Kong - Roebuck, Derek (HKU Press law series., 1994)
Produced in collaboration with the Chartered Institute of Bankers Hong Kong Centre, this book is indispensable to students sitting for the institute's examination from September 1992 onwards, and to anyone involved in the banking industry in Hong Kong.